A new species of Limnophyes Eaton (Diptera: Chironomidae) from Xizang, China - Song, Chao; Zheng, Jiacheng; Wang, Xinhua; Qi, Xin (Zootaxa, 2020)
A new species of the genus Limnophyes Eaton, 1875 from Xizang, China is described and figured based on adult males. Limnophyes nudus sp. nov. belongs to the minimus group and can be easily separated from other species by antenna with 13 flagellomeres, higher AR of 0.85–1.00, bluntly triangular anal point, phallapodeme with ring-like appendix, inferior volsella bare and gonostylus with bubble-like inner margin.